In Association with the Ancestral Customs Pharisaic Ancestral Traditions as a Semi-Private Association Code in Matthew 15 and Antiquitates judaicae 13 - Krause, Andrew R. (2015)
Scholars have long believed that the “ancestral customs” of the Pharisees mentioned in texts such as Antiquitates judaicae 13.297 and Matt 15:1-9 were proto-rabbinic oral tradition, based on apparently corroborating readings of Rabbinic works. However, in this article, I will show that this terminology should be understood within the context of the codes of Graeco-Roman associations. Such language is consistent with both the use of association terminology elsewhere in Josephus, as well as with the corpus of association-related inscriptions and papyri presently extant. The idea of the Pharisees as a semi-private association is not unique, though this terminology provides further corroboration that the Pharisees were understood as a semi-private, itinerant association by contemporary Jewish writers.
Keywords: Josephus -- Gospel of Matthew -- Pharisees -- semi-private association -- association code